Electrochemical synthesis and corrosion performance of polypyrrole and poly(pyrrole-co-aniline) films on copper - Viray, Angeline S. (Transactions of the National Academy of Science and Technology, 2011)
The cheapest and most commonly used metal to date is copper, which is highly prone to corrosion. However, copper is mostly used in highly corrosive environment, which degrades the metal's durability and costs money to multinational businesses. To protect metals, conducting polymers are on of the most promising materials. In thi sudy, the electropolymerization of polypyrrole and poly(pyrrole-co-aniline) on copper electrode was done with cyclic voltammetry. A 0.1M pyrrole (Py) in 0.1M near neutral (pH 7.6) Na2C2O4 solution was used and as a potential window of -0.5 to +1.8V. For the preparation of poly(pyrrole-co-aniline), a 0.1M monomer solution of 0.5 M pyrrole and 0.5M aniline were used. The corrosion protection properties of these polymers were studied using the open circuit potential (OCP) measurement in 3.5% NaCl (aq). PPy had the best corrosion protection properties, followed by poly(pyrrole-co-aniline). PPy showed the response going towards more positive potentials compared to the copolymer and bare copper upon immersion to saline solution, which is due to both the pseudo-layer of copper oxalate complexes formed on the copper surface before polymerization and the polymer coat synthesized its surface. SEM micrographs showed that polypyrrole exhibited multiple layer synthesized on the surface of copper, which contributed to its efficiency on protecting copper from corrosion.